2023
DOI: 10.1038/s41467-023-36871-9
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling two distinct polymorph transition mechanisms in one n-type single crystal for dynamic electronics

Abstract: Cooperativity is used by living systems to circumvent energetic and entropic barriers to yield highly efficient molecular processes. Cooperative structural transitions involve the concerted displacement of molecules in a crystalline material, as opposed to typical molecule-by-molecule nucleation and growth mechanisms which often break single crystallinity. Cooperative transitions have acquired much attention for low transition barriers, ultrafast kinetics, and structural reversibility. However, cooperative tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…47,48 In turn, the mode of temperature variation can be preset to control the expansion or the contraction of the crystal. Since the two polymorphs are expected to have different properties, 49–53 we suggest that this thermal control over the phase transition could be applied for continuous, bidirectional actuation of other objects.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 In turn, the mode of temperature variation can be preset to control the expansion or the contraction of the crystal. Since the two polymorphs are expected to have different properties, 49–53 we suggest that this thermal control over the phase transition could be applied for continuous, bidirectional actuation of other objects.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work showed that two-dimensional quinoidal terthiophene (2DQTT- o -B) (Figure a) exhibits a rich set of polymorph phase transitions with drastically different electronic properties. ,, Powders and films typically form a metastable polymorph I′ initially (depending on solvent and drying process), which are annealed to the stable polymorph I (Figure b). Additionally, the hysteresis for the II–III transition is substantial at 78 °C, suggesting a large energy barrier for the polymorph transition.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this led to kinetic trapping of a metastable polymorph in crystals at a relatively modest cooling rate of 5 °C min −1 in single crystals. 20 Additionally, polymorph I exhibited high performance as an organic semiconductor with mobilities of 0.22 ± 0.07 cm 2 V −1 s −1 , whereas polymorph III (stable above 220 °C) showed poor mobility, 5 orders of magnitude less than polymorph I at (5.63 ± 4.75) × 10 −5 cm 2 V −1 s −1 measured in organic thinfilm transistors. 3 This offers a compelling opportunity to modulate device behavior by controlling the local crystal structure via laser-induced polymorph transitions, given that polymorph I and III are enantiotropically related and therefore thermally accessible and reversible.…”
Section: ■ Introductionmentioning
confidence: 94%
See 2 more Smart Citations